2018
DOI: 10.3390/ijms19123803
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis of Multipotent Progenitor Cells using the Epigallocatechin Gallate-Modified Gelatin Sponge Scaffold in the Rat Congenital Cleft-Jaw Model

Abstract: Cost-effective and functionalized scaffolds are in high demand for stem-cell-based regenerative medicine to treat refractory bone defects in craniofacial abnormalities and injuries. One potential strategy is to utilize pharmacological and cost-effective plant polyphenols and biocompatible proteins, such as gelatin. Nevertheless, the use of chemically modified proteins with plant polyphenols in this strategy has not been standardized. Here, we demonstrated that gelatin chemically modified with epigallocatechin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The bone-forming capacity of vhEGCG-GS was found to be superior to that of vacuum-heated GS (vhGS). Combined use of vhEGCG-GS with multipotent progenitor cells, such as rat dedifferentiated fat cells and adipose-derived stem cells, resulted in greater bone-forming capacity than use of vhGS with both cells [29]. Based on these studies using vhEGCG-GS and vhGS, we hypothesized that postoperative modulation of MMP expression around the implanted materials may contribute to the bone-forming capacity of gelatin-based bone regenerative materials.…”
Section: Introductionmentioning
confidence: 99%
“…The bone-forming capacity of vhEGCG-GS was found to be superior to that of vacuum-heated GS (vhGS). Combined use of vhEGCG-GS with multipotent progenitor cells, such as rat dedifferentiated fat cells and adipose-derived stem cells, resulted in greater bone-forming capacity than use of vhGS with both cells [29]. Based on these studies using vhEGCG-GS and vhGS, we hypothesized that postoperative modulation of MMP expression around the implanted materials may contribute to the bone-forming capacity of gelatin-based bone regenerative materials.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, many experiments have used rat bone defect models, such as those related to skull bones, jawbones, and long bones [14,[36][37][38][39], to evaluate the osteogenic ability of biomaterials. Most of these models relied on bone defects produced through surgery, which undoubtedly stimulate the body's self-repair function, but cannot truly reflect the osteogenic ability of new biomaterials [40]. Recently, Yaguu et al [41] reported that establishing the rat mandibular union as a congenital split jaw model is of great significance for clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of the quantity of EGCG and gelatin in AC-vhEGCG-GSs affected the bone formation results 18,24) . Although both AC-vhEGCG-GSs and vacuum-heated gelatin sponges successfully served as scaffolds for cells, the combination of AC-vhEGCG-GS with multipotent progenitor cells (dedifferentiated fat cells or adipose-derived stem cells) formed more bone in the congenital bone defects of rat jaws than the combination of vacuum-heated gelatin sponge with the above cells 25) . Additionally, the solution containing the EGCG-modified gelatin impaired RANKL-induced osteoclastogenesis and delayed tooth movement by hindering oxidation 26) .…”
Section: Introductionmentioning
confidence: 99%